Copeptin analysis in endocrine disorders - Moodley, Nareshni (Frontiers in Endocrinology, 2023)
Copeptin is cleaved from the same precursor as arginine vasopressin and is released in equimolar amounts with arginine vasopressin from the posterior pituitary in response to the same stimuli. Its level of stability in the blood, quick and simple analysis, and ease of automation make it much easier to analyze than arginine vasopressin, thereby offering a suitable alternative to measuring arginine vasopressin in endocrine disorders. Research has demonstrated the suitability of copeptin in adults for the differentiation of arginine vasopressin resistance and arginine vasopressin deficiency from primary polydipsia, in addition to the early identification of arginine vasopressin deficiency following pituitary surgery; however, further research is still required in the Syndrome of Inappropriate Antidiuretic Hormone (SIADH) and the pediatric population.